2008
DOI: 10.1614/wt-07-175.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Resistance Monitoring in the Canadian Prairies

Abstract: Weed resistance monitoring has been routinely conducted in the Northern Great Plains of Canada (Prairies) since the mid-1990s. Most recently, random surveys were conducted in Alberta in 2001, Manitoba in 2002, and Saskatchewan in 2003 totaling nearly 800 fields. In addition, nearly 1,300 weed seed samples were submitted by growers across the Prairies between 1996 and 2006 for resistance testing. Collected or submitted samples were screened for group 1 [acetyl-CoA carboxylase (ACCase) inhibitor] and/or group 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 23 publications
5
57
1
1
Order By: Relevance
“…In the three case studies reported above, resistance has quite consistently evolved after several years of repeated field selection with herbicide . In addition, surveys have shown that triallate resistance in A. fatua across Canada has declined to low frequencies, most likely because triallate use has significantly decreased over time . However, in all three genera Avena , Echinochloa and Lolium it has been shown that cross‐resistance can occur, and that it is quite a complex phenomenon and not always directly or logically related to the herbicide selection history.…”
Section: Discussionmentioning
confidence: 73%
“…In the three case studies reported above, resistance has quite consistently evolved after several years of repeated field selection with herbicide . In addition, surveys have shown that triallate resistance in A. fatua across Canada has declined to low frequencies, most likely because triallate use has significantly decreased over time . However, in all three genera Avena , Echinochloa and Lolium it has been shown that cross‐resistance can occur, and that it is quite a complex phenomenon and not always directly or logically related to the herbicide selection history.…”
Section: Discussionmentioning
confidence: 73%
“…In Canada, field surveys of wild oat (Avena fatua) revealed the extent of resistance to ACCase and acetolactate synthase (ALS)-inhibiting herbicides (Beckie et al 1999(Beckie et al , 2004(Beckie et al , 2008Legere et al 2000). Work in eastern Australia reveals wild oat to be common in cropping regions throughout New South Wales and southern Queensland (Whalley and Burfitt 1972), with more recent survey work revealing the development of herbicide-resistant wild oat (Nietschke et al 1996;Broster et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides effectively remove crop weeds, minimizing their damaging effects on food production and thereby underpinning global food security. Additionally, herbicide technology has facilitated and driven the worldwide adoption of the sustainable and highly productive conservation cropping systems based on minimal soil disturbance and maximum crop residue retention (Beckie et al, 2008; D'Emden et al, 2008; Thomas et al, 2007). The adoption of conservation cropping systems dramatically increased following the introduction of herbicide‐tolerant crops but so too did the reliance on herbicidal weed control (Christoffoleti et al, 2008; Johnson et al, 2009; Kumar et al, 2008; Powles and Shaner, 2001).…”
mentioning
confidence: 99%
“…This herbicide dependence is resulting in the global evolution of herbicide resistance in important weeds of grain crops. Herbicide resistance evolution now threatens global grain productivity in the five major grain exporting nations: the United States, Brazil, Argentina, Canada, and Australia (Beckie et al, 2008; Christoffoleti et al, 2008; Heap, 2011; Owen et al, 2007; Powles and Shaner, 2001; Scott et al, 2009; Walsh et al, 2007; Webster, 2005).…”
mentioning
confidence: 99%